Taxonomic and functional nestedness of bird communities in urban parks of Liuzhou, China - Binqiang Li; Nehafta Bibi; Shanjun Ma; Wenxuan Chen; Miaodan Yang; Na Xiang; Qingjiang Cui; Lifeng Tan (Biodiversity Data Journal)
Urbanisation significantly impacts the composition and distribution of species through habitat loss and fragmentation. Nestedness is a significant pattern often observed in species assemblages on islands or within fragmented systems. However, numerous studies on nestedness have focused on species richness and composition, neglecting the role of species traits in generating and explaining nestedness. To determine whether functional nestedness follows the same pattern as taxonomic nestedness. In this study, we examined the nestedness patterns of bird assemblages (all birds, passerines, insectivorous, omnivorous and resident birds) across 17 urban parks in Liuzhou of Guangxi Province, China, focusing on taxonomic and functional nestedness. From April 2021 to February 2022, we conducted line transect surveys of bird communities, with three surveys during the breeding season and three surveys during the non-breeding season. In total, we documented 95 bird species. Taxonomic nestedness was assessed using NODF (a nestedness metric, based on overlap and decreasing fill) and WNODF (weighted nestedness metric, based on overlap and decreasing fill) metrics, while functional nestedness was evaluated using treeNODF. Our results showed that none of the birds, passerines, insectivorous, omnivorous and resident birds in Liuzhou urban parks exhibited significant nestedness patterns. However, the nested pattern strongly depended on the choice of the null model. In contrast, as the park area gradually decreases, we observed significant functional nestedness, implying that the trait loss in parks with decreasing area follows an ordered pattern, where smaller parks represent nested subsets of functional traits found in larger parks. From the perspective of species conservation, we recommend prioritizing the protection of larger urban parks to support species with larger habitat requirements. All in all, our findings highlight the importance of considering both taxonomic and functional nestedness in urban biodiversity conservation.